Community‐Driven Code Comparisons for Three‐Dimensional Dynamic Modeling of Sequences of Earthquakes and Aseismic Slip. Issue 3 (10th March 2022) - Jiang, Junle; Erickson, Brittany A.; Lambert, Valère R.; Ampuero, Jean‐Paul; Ando, Ryosuke; Barbot, Sylvain D.; Cattania, Camilla; Zilio, Luca Dal; Duan, Benchun; Dunham, Eric M.; Gabriel, Alice‐Agnes; Lapusta, Nadia; et al.
Abstract: Dynamic modeling of sequences of earthquakes and aseismic slip (SEAS) provides a self‐consistent, physics‐based framework to connect, interpret, and predict diverse geophysical observations across spatial and temporal scales. Amid growing applications of SEAS models, numerical code verification is essential to ensure reliable simulation results but is often infeasible due to the lack of analytical solutions. Here, we develop two benchmarks for three‐dimensional (3D) SEAS problems to compare and verify numerical codes based on boundary‐element, finite‐element, and finite‐difference methods, in a community initiative. Our benchmarks consider a planar vertical strike‐slip fault obeying a rate‐ and state‐dependent friction law, in a 3D homogeneous, linear elastic whole‐space or half‐space, where spontaneous earthquakes and slow slip arise due to tectonic‐like loading. We use a suite of quasi‐dynamic simulations from 10 modeling groups to assess the agreement during all phases of multiple seismic cycles. We find excellent quantitative agreement among simulated outputs for sufficiently large model domains and small grid spacings. However, discrepancies in rupture fronts of the initial event are influenced by the free surface and various computational factors. The recurrence intervals and nucleation phase of later earthquakes are particularly sensitive to numerical resolution and domain‐size‐dependent loading. Despite such variability, key properties of individual earthquakes, including rupture style, duration, total slip, peak slip rate, and stress drop, are comparable among even marginally resolved simulations. Our benchmark efforts offer a community‐based example to improve numerical simulations and reveal sensitivities of model observables, which are important for advancing SEAS models to better understand earthquake system dynamics. Plain Language Summary: Earthquakes and fault zone processes occur over time scales ranging from milliseconds to millennia and longer. Computational models are increasingly used to simulate sequences of earthquakes and aseismic slip (SEAS). These simulations can be connected to diverse geophysical observations, offering insights into earthquake system dynamics. To improve these simulations, we pursue community efforts to design benchmarks for 3D SEAS problems. We involve earthquake researchers around the globe to compare simulation results using different numerical codes. We identify major factors that contribute to the discrepancies among simulations. For example, the spatial dimension and resolution of the computational model can affect how earthquakes start and grow, as well as how frequently they recur. Code comparisons are more challenging when we consider the Earth's surface in the simulations. Fortunately, we find that several key characteristics of earthquakes are accurately reproduced in simulations, such as the duration, total movement, maximum speed, and stress change on the fault, even when model resolutions are not ideal. These exercises are important for promoting a new generation of advanced models for earthquakes. Understanding the sensitivity of simulation outputs will help test models against real‐world observations. Our community efforts can serve as a useful example to other geoscience communities. Key Points: We pursue community efforts to develop code verification benchmarks for three‐dimensional earthquake rupture and crustal faulting problems We assess the agreement and discrepancies of seismic and aseismic fault behavior among simulations based on different numerical methods Our comparisons lend confidence to numerical codes and reveal sensitivities of model observables to major computational and physical factors